Volumetric, topographic and structural changes of orbital apex soft tissues in optic neuropathy caused by edematous exophthalmos - O. Yu. Yatsenko (Oftalʹmologiâ)
Aim. To investigate orbital apex structures in optic neuropathy (ON) due to edematous exophthalmos.Materials and methods. 172 edematous exophthalmos patients were examined. In 46 patients, ON was diagnosed. These patients were divided into 2 groups: early ON (29 patients / 58 eyes) and advanced ON (17 patients / 33 eyes). Standard computed tomography (1‑mm axial and frontal scanning) was performed in all patients.Results.The volume of the orbit and its apex in ON patients was the same as the one in healthy individuals. However, the volume of extraocular muscles was increased in general (5.04±0.07 cm3 in early ON and 6.53±0.044 cm3 in advanced ON) and in orbital apex (1.56±0.02 cm3 and 2.4±0.036 cm3, respectively). The ratio of total orbit volume to extraocular muscles volume was reduced to 5.05 in early ON and to 3.9 in advanced ON. The ratio of orbital apex volume to extraocular muscles volume was reduced to 2.87 and 2.007, respectively.Conclusion. In ON, the volume of extraocular muscles in orbital apex is significantly increased. This results in the severe disturbance of anatomic topographic relations of orbital soft tissues and the compression of neurovascular bundles.